2018
DOI: 10.1111/gcb.14369
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of global vegetation greenup from combined effects of climate change and human land management

Abstract: Global warming and human land management have greatly influenced vegetation growth through both changes in spring phenology and photosynthetic primary production. This will presumably impact the velocity of vegetation greenup (Vgreenup, the daily rate of changes in vegetation productivity during greenup period), yet little is currently known about the spatio-temporal patterns of Vgreenup of global vegetation. Here, we define Vgreenup as the ratio of the amplitude of greenup (Agreenup) to the duration of greenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 102 publications
(180 reference statements)
4
48
1
1
Order By: Relevance
“…This is similar to the conclusion of this study. From this is can be seen that globally, warming has increased Vgreenup in temperature-constrained high latitude forest ecosystems and arctic regions, but decreased Vgreenup in those areas known to be temperate and arid/semi-arid [27].…”
Section: Discussionmentioning
confidence: 94%
“…This is similar to the conclusion of this study. From this is can be seen that globally, warming has increased Vgreenup in temperature-constrained high latitude forest ecosystems and arctic regions, but decreased Vgreenup in those areas known to be temperate and arid/semi-arid [27].…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, this study could overestimate the influence of CO 2 on the RVG trends. Previously, Wang et al (2018) suggested that human land management played an important role on the acceleration of green-up velocity on a global scale. In the present study, we focus on high-latitude regions where human-managed ecosystems are minor, but this anthropogenic influence or other environmental factors could exert an effect on the long-term RVG trends.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that the RVG is a dynamic factor which responds to the changes in environmental conditions and transforms the entire shape of the green-up stage together with the growth onset (Kern et al, 2020;Klosterman et al, 2018;Park et al, 2015). Wang et al (2018) presented that the RVG accelerated over the past several decades from a global perspective. They pointed out that global warming could be the reason of the acceleration based on correlations of the RVG with temperature and precipitation.…”
mentioning
confidence: 96%
“…It is an important link that connects climate change, human activities, and ecosystems. Climate and human activities are the basic drivers for controlling and affecting the spatial distribution of vegetation and its changes [1][2][3]. Climatic factors control the growth process of vegetation on a long-term scale, restrict the geographical distribution of terrestrial vegetation, and determine the type and magnitude of regional ecosystem services.…”
Section: Introductionmentioning
confidence: 99%